Advancement of Nanofibrous Mats and Common Useful Drug Delivery Applications. (19th April 2022) - Abu Owida, Hamza; Al-Nabulsi, Jamal I.; Alnaimat, Feras; Al Sharah, Ashraf; Al-Ayyad, Muhammad; Turab, Nidal M.; Abdullah, Mustafa
Abstract : Electrospinning enables simple and cost-effective production of polymer nanofibers from different polymer materials. Drug delivery systems are capable of achieving maximum drug treatment benefits by significantly reducing adverse complications. Electrospun nanofibers have recently attracted considerable attention owing to their distinctive properties, including flexibility and biocompatibility. The implementation of functional constituents within nanostructure fibers blends is an effective technique for the administration of a variety of drugs in animal research, broadening the nanofiber capability and reliability. The nanofibrous mesh and its various application purposes are discussed in terms of a summary of recent research, emphasizing the ease of streaming and a large number of combinations of this approach, which could lead to a breakthrough in targeted therapy.